2013
DOI: 10.18632/oncotarget.1420
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial oxidative stress is the achille's heel of melanoma cells resistant to Braf-mutant inhibitor

Abstract: Vemurafenib/PLX4032, a selective inhibitor of mutant BRAFV600E, constitutes a paradigm shift in melanoma therapy. Unfortunately, acquired resistance, which unavoidably occurs, represents one major limitation to clinical responses. Recent studies have highlighted that vemurafenib activated oxidative metabolism in BRAFV600E melanomas expressing PGC1α. However, the oxidative state of melanoma resistant to BRAF inhibitors is unknown. We established representative in vitro and in vivo models of human melanoma resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
135
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(154 citation statements)
references
References 36 publications
17
135
0
2
Order By: Relevance
“…These findings indicate that, in addition to downregulation of glycolytic metabolism, BRAF inhibition alters glycine, myo-inositol, and lipid metabolism, inducing a metabolic shift that is able to maintain cellular energetic status probably by means of activating compensatory pathways, for example, OxPhos (16). Indeed, we observed increased ROS production (to a similar extent as in previous publications; ref.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…These findings indicate that, in addition to downregulation of glycolytic metabolism, BRAF inhibition alters glycine, myo-inositol, and lipid metabolism, inducing a metabolic shift that is able to maintain cellular energetic status probably by means of activating compensatory pathways, for example, OxPhos (16). Indeed, we observed increased ROS production (to a similar extent as in previous publications; ref.…”
Section: Discussionsupporting
confidence: 90%
“…BRAF inhibitor treatment has previously been shown to reactivate mitochondrial OxPhos, leading to increased reactive oxygen species (ROS) levels (13). We thus assessed ROS in WM266.4 cells following exposure to vemurafenib and found that, consistent with a previous report (16), BRAF inhibition in BRAF V600D WM266.4 cells for 24 hours led to a concentration-dependent increase in ROS production (up to 197.8% AE 62.8% of controls; P ¼ 0.03), indicating that OxPhos may also be increased in our cells ( Supplementary Fig. S3).…”
Section: Vemurafenib Induces Differential Glucose Utilization In Brafsupporting
confidence: 85%
See 2 more Smart Citations
“…Second, select targeting of OxPhostype survival mechanisms may have broader implications for resistance mechanisms that enable tumors to escape inhibition of canonical growth factor signaling, including those initiated by BCR, RAS, and BRAF signaling pathways. 7,52,53 Notably, tigecycline is FDA-approved and is being actively developed for its potential therapeutic benefits in several diseases. 54 Our findings warrant investigation of the therapeutic utility of tigecycline and other inhibitors of the mitochondrial translation pathway in DLBCL and other OxPhos-dependent tumors.…”
Section: Discussionmentioning
confidence: 99%